Designing of Compact Low Frequency Vibration Isolator with Quasi-Zero-Stiffness. Issue 4 (December 2015) - Valeev, Anvar; Zotov, Alexey; Kharisov, Shamil
This article considers the design of a compact isolator with quasi-zero stiffness. It has high vibration control properties at low weight and dimensions. Also the developed vibration isolator with quasi-zero stiffness can protect against low-frequency vibration. The vibration isolator is of a passive type, made from a single elastic material, which will be compact and convenient in manufacturing. An analytical study of the vibration isolation, its manufacturing and experimental static study are presented. The natural frequency of the developed vibration isolator with quasi-zero stiffness is less than 1 Hz.